Research Progress on Chemiresistive Carbon Monoxide Sensors - Minghui Wei; Xuerong Shi; Min Zhu; Shengming Zhang; Heng Zhang; Haiyu Yao; Shusheng Xu (Nanomaterials)
The development of high-performance carbon monoxide (CO) sensors is essential for protecting human health, ensuring industrial safety, and maintaining environmental well-being. Among various types of sensors, chemiresistive sensors exhibit considerable promise for real-time applications due to their operational capabilities. To achieve high performances of chemiresistive sensors, this review emphasizes various enhancement strategies, encompassing the refinement of sensing materials, the augmentation of sensor structures, and the optimization of gas recognition algorithms. Specifically, the modification techniques of sensing materials, which include the construction of heterostructures, the decoration with noble metals, surface functionalization, hetero-element-doping, and morphology engineering, are delved into comprehensively. This review provides insights into the rational design of cost-effective CO sensors.